Mechanisms regulating resistance to inhibitors of topoisomerase II - Ganapathi, Ram; Ganapathi, Mahrukh K. (Frontiers in Pharmacology, 2013)
Inhibitors of topoisomerase II are clinically effective in the management of hematological malignancies and solid tumors. The efficacy of anti-tumor drugs targeting topoisomerase II is often limited by resistance and studies with in vitro cell culture models have provided several insights on potential mechanisms. Multidrug-transporters that are involved in the efflux and consequently reduced cytotoxicity of diverse anti-tumor agents suggest that they play an important role in resistance to clinically active drugs. However in clinical trials, modulating the multidrug resistant phenotype with agents that inhibit the efflux pump has not had an impact. Since reduced drug accumulation per se is insufficient to explain tumor cell resistance to topoisomerase II inhibitors several studies have focused on characterizing mechanisms that impact on DNA damage mediated by drugs that target the enzyme. Mammalian topoisomerase IIα and topoisomerase IIβ isozymes exhibit similar catalytic, but different biologic, activities. Whereas topoisomerase IIα is associated with cell division, topoisomerase IIβ is involved in differentiation. In addition to site specific mutations that can affect drug induced topoisomerase II-mediated DNA damage, post-translation modification of topoisomerase II primarily by phosphorylation can potentially affect enzyme-mediated DNA damage and the downstream cytotoxic response of drugs targeting topoisomerase II. Signaling pathways that can affect phosphorylation and changes in intracellular calcium levels/calcium dependent signaling that can regulate site-specific phosphorylation of topoisomerase have an impact on downstream cytotoxic effects of topoisomerase II inhibitors. Overall, tumor cell resistance to inhibitors of topoisomerase II is a complex process that is orchestrated not only by cellular pharmacokinetics but more importantly by enzymatic alterations that govern the intrinsic drug sensitivity.